This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: h ( t ) = x ( t ), and z ( t ) = h ( t ) * x ( t ). Find out the Fourier transform of z ( t ). Question 7: [Basic] Suppose x 1 ( t ) = δ ( tt ) and x 2 ( t ) = U ( t + 2) U ( t2). Find out and plot x 3 ( t ) = x 1 ( t ) * x 2 ( t ) when t = 1. If t changes from 1 to 5, how will your x 3 ( t ) change? Question 8: p. 338, Problem 4.21(b,g,i). Question 9: p. 338, Problem 4.22(b,c,d). Question 10: p. 339, Problem 4.23. Question 11: p. 341, Problem 4.25. (a,b,c) Question 12: p. 341, Problem 4.25. (e) • Do (e) by the Parseval’s relationship. • Evaluate 1 2 π R ∞∞ X ( ω ) e j 2 ω dω . Hint: View it as 1 2 π R ∞∞ X ( ω ) e jωt dω with t = 2, which is the inverse Fourier transform of X ( ω ) evaluated at t = 2....
View
Full Document
 Fall '06
 V."Ragu"Balakrishnan
 π π, fourier transformation

Click to edit the document details